STRATEGI PENANGANAN ANAK TIDAK SEKOLAH DI KABUPATEN SRAGEN - Leny Noviani; Atik Catur Budiarti; Tuhana Tuhana; Martani Setyawati (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
The problem of children not attending school in Sragen is high, namely 9,398 children. This problem have an impact on the quality of human resources and will affect regional competitiveness. The purpose of this research is to identify the factors that cause of children not in attending school and provide alternative solutions for this. This study is descriptive research. The population in this study were children aged 7–18 who had never attended school or dropped out of school. The sample in this study consisted of 1,143 respondents. Data collection techniques used were surveys, FGD, and literature studies. Data analysis techniques: 1) quantitative descriptive analysis to identify the causative factors of the problems; 2) qualitative data analysis to analyze the results of the FGD. The results showed that the causes of this problems: lack of motivation, lack of economic ability, working, disability, family problems, victims of bullying, giving birth to children, and low cognitive abilities. Strategies for dealing: 1) prevention strategies to monitor children who are vulnerable or at risk of dropping out of school; and 2) intervention strategies based on the causes. The intervention strategy aims to return children to appropriate schools or training. This intervention strategy is multisectoral